2004
DOI: 10.1210/jc.2004-031132
|View full text |Cite
|
Sign up to set email alerts
|

Free Fatty Acids Exert an Inhibitory Effect on Adrenocorticotropin and Cortisol Secretion in Humans

Abstract: Free fatty acid (FFA) administration stimulates the hypothalamic-pituitary-adrenal (HPA) axis in rats, suggesting that the HPA axis and lipolysis may be linked by a positive-feedback loop. To clarify the influence of FFA on the HPA axis in humans, we studied the effect of lipid load on both basal and stimulated ACTH and cortisol secretion in normal subjects. In six young female volunteers [(mean +/- SEM) age, 24.4 +/- 2.1 yr; body mass index, 23.1 +/- 1.2 kg/m(2)), ACTH, cortisol, FFA, glucose, and insulin lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
2
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 34 publications
7
28
2
3
Order By: Relevance
“…Studies in humans have suggested that infusion of Intralipid either had no effect or decreased cortisol concentrations. [10][11][12] However, many of these studies were performed under systems that maintained insulin and/or glucose concentrations at predetermined concentrations. Yet, Intralipid infusion in humans did not appear to influence whole-body cortisol metabolism, but did increase conversion of cortisone to cortisol in subcutaneous adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in humans have suggested that infusion of Intralipid either had no effect or decreased cortisol concentrations. [10][11][12] However, many of these studies were performed under systems that maintained insulin and/or glucose concentrations at predetermined concentrations. Yet, Intralipid infusion in humans did not appear to influence whole-body cortisol metabolism, but did increase conversion of cortisone to cortisol in subcutaneous adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…FFAs possess an electrophysiological effect on the central nervous system where they can be incorporated by central nervous system cells (44,45). Indeed, we have demonstrated that a lipid loadinduced increase in circulating FFA levels in healthy adult subjects exerts an inhibitory effect on spontaneous ACTH and cortisol secretion (11). Thus, we hypothesized some refractoriness of the enhanced HPA activity to lipid load in this pathological condition.…”
Section: Discussionmentioning
confidence: 91%
“…To increase the lipoprotein lipase activity, heparin was added to the suspension. We chose an Intralipid dose equivalent to that used in many studies focusing on the effects of FFAs on GH secretion in normal subjects and anorectic patients (1,3,4,38) and on HPA axis activity in normal subjects (11) and which showed a clear inhibitory effect on both somatotroph and corticotroph function. Blood samples were taken every 30 min from 0 to 180 min.…”
Section: Eightmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcome measures of patients after anesthesia with propofol, isoflurane alone or in combination with Intralipid ® for laparoscopic inguinal hernia repair. have contributed to the accentuated proinflammatory profile in these groups [34][35][36][37]. More specifically, the inflammatory responses to stress involve coordinated and complex reactions of the immune, nervous, and endocrine systems.…”
Section: Propofolmentioning
confidence: 99%